Clinical benefit of treatment with eribulin mesylate for metastatic triple‐negative breast cancer: Long‐term outcomes of patients treated in the US community oncology setting. (31st July 2018) - Mougalian, Sarah S.; Copher, Ronda; Kish, Jonathan K.; McAllister, Lindsay; Wang, Zhixiao; Broscious, Mary; Garofalo, David; Radtchenko, Janna; Feinberg, Bruce A.
Abstract: Introduction: Real‐world data are critical to demonstrate the consistency of evidence and external generalizability of randomized controlled trials (RCTs). This study examined characteristics and outcomes of metastatic triple‐negative breast cancer (mTNBC) patients treated with eribulin mesylate at community oncology practices in the United States. Methods: Physicians identified mTNBC patients initiating eribulin between 1 January 2011 and 1 January 2014 and abstracted data into an electronic case report form (eCRF). Eribulin treatment in the metastatic setting was categorized as early use (EU, first‐/second‐line) and late use (LU, third‐line or later). Patient characteristics, overall survival (OS), disease response (per treating physician), and adverse events (AEs) rates in each group, respectively, are reported. Results: Overall 252 eCRFs were completed: 125 (49.6%) EU and 127 (50.4%) LU. The median age at metastatic diagnosis was 53 years and 42.1% were stage IV at their initial diagnosis. The median duration of follow‐up from the initiation of first‐line treatment was 24 months. Rates of disease response (complete or partial per treating physician) were 69.9% in the EU group and 48.8% in the LU group. The five most commonly reported adverse events during eribulin were as follows: fatigue (65.1%), weakness (40.1%), decreased appetite (32.5%), neutropenia (31.0%), and leukopenia (27.4%). Discontinuation of eribulin due to AE was observed in 4.0% of patients. Median OS from initiation of eribulin was 23.0 months (95% CI: 18.7‐27.3) among EU and 14.7 (95% CI: 12.6‐16.9) among LU. Conclusion: In the real‐world eribulin‐treated mTNBC, patients have more sites of metastatic disease and exposure to greater numbers of prior therapies compared to RCTs. The median OS of 14.7 months among LU patients is consistent with, and slightly longer than the 13.1 months and 14.4 months reported in the EMBRACE and Study 301 clinical trials, respectively. Abstract : This study examined real‐world outcomes of treatment with eribulin mesylate in 252 women with metastatic triple‐negative breast cancer patients in the US. Patients were categorized according to line of usage of eribulin (early vs late). We found that patients treated with eribulin in the real‐world setting have more sites of metastatic disease and exposure to greater numbers of prior therapies compared to trial patients, with median OS consistent with that seen in clinical trials.